Tantangan Implementasi Coding dan Artificial Intelligence dalam Kurikulum Nasional: Perspektif Keadilan dan Kesiapan Pembelajaran - Hilmy Shalahudin Nasyor; Nur Marliza Rahmi Afdinillah; Husniyatus Salamah Zainiyati; Hanun Asrohah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The Indonesian government has included coding and AI in the national curriculum to improve students' digital literacy, but there are obstacles to implementation in disadvantaged areas. This journal aims to identify barriers ranging from technological infrastructure readiness and teacher competence to socio-cultural aspects that affect the implementation of coding and AI learning in disadvantaged areas. The method used is a qualitative literature study with thematic analysis of various reliable sources to obtain a comprehensive overview and strategic solutions. The results show that limited electricity, internet access, and technological devices are the main obstacles, accompanied by a lack of teacher training and a curriculum that is not adaptive to local conditions. In addition, the gap in students' digital literacy and socio-cultural attitudes are also hindering factors. The gap between the idealism of national policy and the reality on the ground is an important focus that has not been studied in depth. Previous studies have mostly described general obstacles without taking into account the specific geographical and socioeconomic factors of disadvantaged areas. Contextual implementation strategies, intensive teacher training, optimization of alternative infrastructure, and the involvement of various stakeholders are considered key to the successful equitable distribution of technology learning in disadvantaged areas. This study makes an important contribution to the development of inclusive and equitable technology education in Indonesia.